2018
DOI: 10.1590/1807-1929/agriambi.v22n8p541-546
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization to attenuate the damages caused by salinity on yellow passion fruit seedlings

Abstract: The study aimed to evaluate the mitigating effect of nitrogen (N) on the damages caused by irrigation water salinity, in the production of yellow passion fruit seedlings. A randomized block design in split plots was used, with five levels of irrigation water salinity (plot) (0.3, 1.0, 1.7, 2.4 and 3.1 dS m-1) and five doses of N fertilization (sub-plot) (180, 240, 300, 360 and 420 mg of N dm-3), with five replicates, totaling 125 experimental units, with one plant per plot. The seedlings were produced in 3.780… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
2
0
2
Order By: Relevance
“…2021 Cavalcante, Dias, Nascimento and Freire (2011) observed a reduction in the photosynthetic efficiency of passion fruit plants subjected to irrigation with saline water at an electrical conductivity above 2.5 dS m -1 , at 448 days after transplanting. Wanderley et al (2018) also observed similar effects on sour passion fruit seedlings when subjected to increasing levels of electrical conductivity in irrigation water, from 0.3 to 3.1 dS m -1 .…”
Section: Resultssupporting
confidence: 57%
“…2021 Cavalcante, Dias, Nascimento and Freire (2011) observed a reduction in the photosynthetic efficiency of passion fruit plants subjected to irrigation with saline water at an electrical conductivity above 2.5 dS m -1 , at 448 days after transplanting. Wanderley et al (2018) also observed similar effects on sour passion fruit seedlings when subjected to increasing levels of electrical conductivity in irrigation water, from 0.3 to 3.1 dS m -1 .…”
Section: Resultssupporting
confidence: 57%
“…Resultados semelhantes foram relatados por Wanderley et al (2018) em mudas de maracujazeiro, no qual a salinidade da água de irrigação reduziu a altura em cerca de 12,2 cm por unidade com o aumento da salinidade, que resultaram em declínio de 34,18 cm (25,18%), e também do diâmetro do caule em 0,196 mm por unidade em incrementos na CEa.…”
Section: Resultsunclassified
“…Diante disso, inúmeras pesquisas foram e vem sendo realizados no intuito de avaliar a interação salinidade e nitrogênio em diversas culturas, como goiaba (BEZERRA et al, 2018;SOUZA et al, 2017), maracujazeiro amarelo (WANDERLEY et al, 2018), milho (SOUSA et al, 2021RIBEIRO et al, 2020;BRAZ et al, 2019;LACERDA et al, 2016;AZIZIAN;SEPASKHAH, 2014), algodão (RIBEIRO et al, 2020;LIMA et al, 2018;CHEN et al, 2010).…”
Section: ____________________________________________________________...unclassified